Analisis Implementasi Evaluasi Komprehensif Hasil Belajar Al-Qur’an Melalui Tes Tertulis Dan Observasi - Chaiza Salsabila; Dzakiyyah Faza El Fitri; Achmad Hunaifi Ramadhan; Ahmad Yusam Thobroni (At-Tarbiyah: Journal of Islamic Religious Research and Education, 2026)
Comprehensive evaluation in Quranic education through written tests and observation is a crucial approach for assessing students’ abilities in a holistic manner. A comprehensive evaluation approach is essential for assessing students’ abilities in their entirety. Such evaluations not only test memorization but also their understanding, attitudes, and skills. However, in reality, current evaluation practices often remain focused solely on memorization. Consequently, students’ learning outcomes are not fully reflected. This study aims to examine how the implementation of comprehensive evaluation can support the improvement of the quality of Quranic education. This study employs a qualitative method with a literature review approach through the analysis of relevant literature. The results of this study indicate that comprehensive assessment can assist teachers in understanding students’ abilities more thoroughly and in improving the quality of learning. Furthermore, the implementation of comprehensive evaluation is also capable of measuring students’ competencies holistically, not only in cognitive aspects but also in psychomotor and affective aspects. Through this evaluation model, the quality of each student and graduate can be better assessed, thereby making the learning process more effective, focused, and aligned with educational objectives. Keywords: Comprehensive Evaluation; Qur’anic Learning; Written Test; Observation; Learning Quality